Nikolaj Ivanovič Nikolaev, La critica non ufficiale al «metodo formale» nella cultura russa degli anni ‘20 (ENTHYMEMA, 2011)
The history of Russian Formalism is complex and manifold. For a long time now, researches on this topic have been unveiling its contradictions and internal quarrels, as well as its tangled network of relationships with personalities, who belonged to contemporary circles and literary groups. The article that is here presented in translation – and that is the second part of three – aims to shed a light on the activity of the unofficial critics of the Russian Formalism. This means shedding a light on the history of all the intellectuals – either as individuals or as belonging to specific aesthetic-literary movement – who, either in Moscow or Petrograd/Leningrad – proposed a methodological alternative to the critical praxis of Ėjchenbaum’s group. More specifically, this essay focuses on the activity of such scholars as Grigorij Vinokur and Viktor Žirmunskij, as well as on the disciples of the philosopher Gustav Špet, who worked in the Muscovite GAChN.